A discrete-time system with service control and repairs - Atencia, Ivan (Zielona Góra: Uniwersytet Zielonogórski)
This paper discusses a discrete-time queueing system with starting failures in which an arriving customer follows three different strategies. Two of them correspond to the LCFS (Last Come First Served) discipline, in which displacements or expulsions of customers occur. The third strategy acts as a signal, that is, it becomes a negative customer. Also examined is the possibility of failures at each service commencement epoch.
Keywords: discrete-time queue; unreliable server; negative customers; busy period; sojourn times; continuous-time counterpart